Lockdown Lives: A Longitudinal Study of Inter-Relationships Among Feelings of Loneliness, Social Contacts, and Solidarity During the COVID-19 Lockdown in Early 2020. (September 2022) - van Breen, Jolien A.; Kutlaca, Maja; Koç, Yasin; Jeronimus, Bertus F.; Reitsema, Anne Margit; Jovanović, Veljko; Agostini, Maximilian; Bélanger, Jocelyn J.; Gützkow, Ben; Kreienkamp, Jannis; Abakoumkin, Georgios; Khaiyom, Jamilah Hanum Abdul; et al.
We examine how social contacts and feelings of solidarity shape experiences of loneliness during the COVID-19 lockdown in early 2020. From the PsyCorona database, we obtained longitudinal data from 23 countries, collected between March and May 2020. The results demonstrated that although online contacts help to reduce feelings of loneliness, people who feel more lonely are less likely to use that strategy. Solidarity played only a small role in shaping feelings of loneliness during lockdown. Thus, it seems we must look beyond the current focus on online contact and solidarity to help people address feelings of loneliness during lockdown. Finally, online contacts did not function as a substitute for face-to-face contacts outside the home—in fact, more frequent online contact in earlier weeks predicted more frequent face-to-face contacts in later weeks. As such, this work provides relevant insights into how individuals manage the impact of restrictions on their social lives.